Silver-mediated radical 5-exo-dig cyclization of 2-alkynylbenzonitriles: synthesis of phosphinylated 1-indenones. Issue 51 (26th May 2017) - Zhu, Xiao-Tong; Zhao, Qi; Liu, Feng; Wang, Ai-Fang; Cai, Pei-Jun; Hao, Wen-Juan; Tu, Shu-Jiang; Jiang, Bo
Abstract : A new silver-mediated 5- exo-dig cyclization of 2-alkynylbenzonitriles with disubstituted phosphine oxide and H2 O has been developed. Abstract : A new silver-mediated 5- exo-dig cyclization of 2-alkynylbenzonitriles with disubstituted phosphine oxide and H2 O has been developed. The reaction enables multiple bond-forming events including C–P, C–C and C–O bonds under atmospheric conditions, leading to the concise and direct formation of 28 examples of phosphorus-containing 1-indenones with generally good yields.